Pengaruh Kualitas Pelayanan dan Harga terhadap Minat Berkunjung Kembali Konsumen di RM. Putra Cangkuang - Oktapiani, Saskia Dewi; Herawati, Siti (Universitas Batanghari, 2024)
Examining how pricing and service quality affect customers' desire to visit Rm Putra Cangkuang again is the goal of this study. This study employed a quantitative methodology. The participants in this study were guests of Rm Cangkuang's son, who lives in Garut City and has made multiple visits. Ninety samples were selected, and primary data was the data source utilized. A cross-sectional or one-shot study is the method of data gathering that is employed. Descriptive analysis, multiple regression, classical assumptions, multicollinearity, heteroscedasticity, normalcy, and hypothesis testing are the data analysis approaches that are employed. The study's findings show that interest in going back is positively impacted by both pricing and service quality.